FERMENTASI LIMBAH PADAT INDUSTRI TEPUNG AREN SEBAGAI SUMBER SERAT UNTUK TERNAK RUMINANSIA - - Mansyur; I. Susilawati; N. P. Indrani; R.Z. Islami; T. Dhalika (Udayana University)
The aim of research is to knows the effect of additive addition on solid waste from Arengan pinnata mills industry. A randomize complete design was used in this research. The treatments are addition of 5% molasses (P1), addition of 5% sludge of soy souce industry (P2), addition of 1% Urea (P3), addition of 5% molasses and 1% Urea (P4), and addition of 5% sludge of soy souce industry and 1% Urea (P5). Each treatment was replicated 4 times. The observe objects are degree of acidity, lactic acid dan ammonia content, contents of fiber fraction (Neutral Detergent Fiber, NDF; and Acid Detergent Fiber, ADF), crude protein content, ammonia production in rumen, and in vitro digestibility dry matter (IVDDM) and in vitro digestibility organic matter (IVDOM). Data were analyzed by variant analyses, and followed by Duncan Multipel Range Test. The research result showed that the treatments significantly effected on degree of acidity, lactic acid dan ammonia content, contents of fiber fraction (Neutral Detergent Fiber, NDF; and Acid Detergent Fiber, ADF), crude protein content, ammonia production in rumen, and in vitro digestibility dry matter (IVDDM) and in vitro digestibility organic matter (IVDOM). Addition 1% Urea and 5% Sludge of soy souce industry is the best result on nutrition quality of solid waste from arenga pinnata mills.